PENGARUH METODE PROBLEM BASED LEARNINGDAN METODE INQUIRY TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN PADA SISWA KELAS VII MTS MIFTAHUL MUBTADIIN - Siti Mukarromah; Sunardjo; Dian Eka Indriani (Penerbit STKIP PGRI Bangkalan, 2019)
Civics Education is a course that aims to educate students to foster morals and become a good citizen, which are expected to be realized in daily life, both in the school environment and outside the school environment. Civics education should be able to shape activeness , creativity, and intelligent thinking of students in solving any existing problem by way of consensus agreement in accordance with the 4th-point Pancasila precepts namely